2013
DOI: 10.1007/s00590-013-1381-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of partial fibulectomy on contact pressure of the knee: a cadaveric study

Abstract: The current study demonstrated partial fibulectomy at 12 cm above lateral malleolus results in decreasing pressure in knee medial compartment and increasing pressure in knee lateral compartment. Further studies are needed to evaluate the clinical importance of partial fibulectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 5 publications
0
17
0
4
Order By: Relevance
“…Some cadaveric experiments have uncovered that PFO can reduce stresses in the medial compartment of the knee. Yazdi et al [23] have cut off the 20-mm long proximal fibulae in 6 cases and have found that the overall knee joint stress has been reduced, revealing a more significant decrease in the medial compartment stress with the maximum decrease of 21.6% and an increase in the lateral compartment stress with the maximum increase of 12.9%. In our finite element experiment, PFO changed the stress distribution in the knee joint and reduced the medial compartment stress especially in KOA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some cadaveric experiments have uncovered that PFO can reduce stresses in the medial compartment of the knee. Yazdi et al [23] have cut off the 20-mm long proximal fibulae in 6 cases and have found that the overall knee joint stress has been reduced, revealing a more significant decrease in the medial compartment stress with the maximum decrease of 21.6% and an increase in the lateral compartment stress with the maximum increase of 12.9%. In our finite element experiment, PFO changed the stress distribution in the knee joint and reduced the medial compartment stress especially in KOA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Partial fibulectomy is a procedure commonly used to harvest bone graft or to treat nonunion of tibial fractures or fibular fractures. One previous cadaveric study revealed that partial fibulectomy at 12 cm above the lateral malleolus resulted in decreased pressure in the medial compartment and increased pressure in the lateral compartment of the knee joint. However, this study was irrelevant to knee OA.…”
Section: Introductionmentioning
confidence: 94%
“…Proximal fibular osteotomy indirectly initiates KOA and promotes its progression as it is based on the 'theory of differential settlement' [7]. Minimal trauma, few complications, definite effects and wide clinical applications are the characteristics of this treatment approach [8]. The available evidence on the benefits of proximal fibular osteotomy was analyxed by this study.…”
Section: Introductionmentioning
confidence: 88%
“…With increasing grade of OA of the knee, femoral neckshaft valgus angle decreases and lateral bowing of the femoral shaft increases, reducing the condylar shaft angle and shifting the mechanical axis medially, whereas on the tibial side, especially in the early stages of OA tibial plateau compression leads to a steepening of medial plateau more than bowing of tibia, [8].Progress of medial OA occurs more due to medial tibial compression rather than to bowing of the tibia [8]. The apparent density of trabeculae, trabecular architecture and the strength of the bone material are the determinants of compressive strength and stiffness of trabecular bone [9].…”
Section: Biomechanics Of Varus Knee Osteoarthritismentioning
confidence: 99%